2012
DOI: 10.1111/j.1600-6143.2011.03840.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Causes of Kidney Transplant Failure: The Dominant Role of Antibody-Mediated Rejection and Nonadherence

Abstract: We prospectively studied kidney transplants that progressed to failure after a biopsy for clinical indications, aiming to assign a cause to every failure. We followed 315 allograft recipients who underwent indication biopsies at 6 days to 32 years posttransplant. Sixty kidneys progressed to failure in the followup period (median 31.4 months). Failure was rare after T-cell-mediated rejection and acute kidney injury and common after antibody-mediated rejection or glomerulonephritis. We developed rules for using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
1,180
12
37

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,378 publications
(1,264 citation statements)
references
References 37 publications
35
1,180
12
37
Order By: Relevance
“…Thus, it is important to define these survival issues in terms of actual phenotypes of failure, by studies attributing causality to observed kidney failures. In our attribution analysis (52), we found some kidneys that fail in the context of intercurrent medical illnesses, possibly explaining the impact of recipient age (and age-related comorbidities) on death censored late kidney loss as well as recipient death (52).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to define these survival issues in terms of actual phenotypes of failure, by studies attributing causality to observed kidney failures. In our attribution analysis (52), we found some kidneys that fail in the context of intercurrent medical illnesses, possibly explaining the impact of recipient age (and age-related comorbidities) on death censored late kidney loss as well as recipient death (52).…”
Section: Discussionmentioning
confidence: 99%
“…After censoring for death, however, similar findings remain, and it is likely that chronic alloimmune damage is a major cause of graft loss in this cohort as reported elsewhere. [28][29][30][31][32] Finally, HLA typing methods have evolved, such that the HLA antigens identified in one donor may be more fully resolved than the other donor or in the recipient. 33 Where this resolution discrepancy existed, we classified the antigens as equivalent.…”
Section: Discussionmentioning
confidence: 99%
“…However, ''IF/TA'' should only be diagnosed if the underlying etiology of fibrosis and tubular atrophy is not clear (5). With protocol biopsies and detailed clinical information a cause of graft dysfunction can be recognized in most cases, with the majority being due to chronic rejection (9,10,12,16). Therefore, within this review we will use not use the term IF/TA but rather discuss renal fibrosis in general given that there is little to no evidence that the allograft fibrosis as part of IF/TA or any other allograft pathology differs significantly from the fibrosis observed in other progressive diseases of native kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…IF/TA is detectable in about 40% of kidney allografts at 3-6 months (6,7) and increases to about 65% at 2 years (8). IF/TA is a non-specific lesion induced by various immune and non-immune injuries to the graft (9,10) and an independent risk factor for late graft loss, particularly in grafts from expanded criteria donors, irrespective of whether a specific disease was diagnosed in the allograft or not (11)(12)(13)(14)(15). However, ''IF/TA'' should only be diagnosed if the underlying etiology of fibrosis and tubular atrophy is not clear (5).…”
Section: Introductionmentioning
confidence: 99%